Electrical Performance and Carbon Deposition Differences between the Bi-Layer Interconnector and Conventional Straight Interconnector Solid Oxide Fuel Cell - Min Yan; Pei Fu; Qiuyang Chen; Qiuwang Wang; Min Zeng; Jaideep Pandit (Energies, 2014)
Carbon deposition considered in a solid oxide fuel cell (SOFC) model may be influenced by the operating voltage, inlet water/methane ratio, working temperature and pressure, inlet molar fraction of fuel and so on. The effects of these parameters in a planar SOFC implementing a novel bi-layer interconnector are not well understood. This paper is focused on the numerical study of carbon deposition and electrical performance of a bi-layer interconnector planar SOFC. The results illustrate that the electrical performance of the bi-layer interconnector SOFC is 11% higher than that of the conventional straight interconnector SOFC with initial state. After 120 days of operation, the electrical performance of the bi-layer interconnector SOFC has a slight decrease and more carbon deposit because of the increased electrochemical reaction rate. However, these differences minimize if higher operating voltages are involved.